2010
DOI: 10.1007/978-3-642-16901-4_27
|View full text |Cite
|
Sign up to set email alerts
|

Trace-Driven Verification of Multithreaded Programs

Abstract: Abstract. We present a new method that combines the efficiency of testing with the reasoning power of satisfiability modulo theory (SMT) solvers for the verification of multithreaded programs under a user specified test vector. Our method performs dynamic executions to obtain both under-and over-approximations of the program, represented as quantifier-free first order logic formulas. The formulas are then analyzed by an SMT solver which implicitly considers all possible thread interleavings. The symbolic analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2012
2012

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…They can be classified in several different ways, considering for example static or dynamic approaches and shared‐memory and/or message‐passing paradigms and also considering the language and/or standard used. The published papers are distributed over a number of discrete testing topics, such as failure injection , formal verification , static analysis , testing‐driven development , controlled execution , mutation testing , model checking , model‐based testing , structural testing , symbolic analysis , search‐based testing , interleaving coverage testing , probabilistic concurrency testing , reachability testing , and test case generation .…”
Section: Related Workmentioning
confidence: 99%
“…They can be classified in several different ways, considering for example static or dynamic approaches and shared‐memory and/or message‐passing paradigms and also considering the language and/or standard used. The published papers are distributed over a number of discrete testing topics, such as failure injection , formal verification , static analysis , testing‐driven development , controlled execution , mutation testing , model checking , model‐based testing , structural testing , symbolic analysis , search‐based testing , interleaving coverage testing , probabilistic concurrency testing , reachability testing , and test case generation .…”
Section: Related Workmentioning
confidence: 99%
“…The rest of the report summarizes the main contributions of our research. More details about our research can be found in our publications [13,37,38,39,45,46,47] and a forthcoming Ph.D. thesis [36].…”
Section: Approach and Outlinementioning
confidence: 99%
“…Para o teste baseado na especificação, são propostas abordagens, como: verificação formal SAKALLAH, 2010;RAKAMARIC, 2010;WOOD et al, 2010;SUGETA et al, 2004;SOUZA et al, 1999) e teste baseado em modelos (AICHERNIG et al, 2009;LI et al, 2009;CORDEIRO, 2010).…”
Section: Trabalhos Relacionadosunclassified